2010
DOI: 10.1016/j.jpainsymman.2009.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrical Nerve Stimulation Induces Vasodilation in Healthy Controls But Not in Refractory Angina Patients

Abstract: High-dose TENS induces forearm vasodilation in healthy subjects but not in patients with RAP. These findings suggest that TENS has different vascular effects in patients with severe coronary artery disease compared with healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Neuromodulation may vary depending on the duration, intensity, and area of application 16 . Previous studies have demonstrated that time of electrical stimulation seem to promote different responses, changes in local circulation 10,[17][18][19] , increase in myocardial oxygen, and reduction in oxygen demand 20 ; however, it is still unclear whether interferential current stimulation can improve blood flow during muscle metaboreflex induction. Indergand and Morgan 10 applied IES for only 10 min 10 , but in our study, the opposite results were obtained when IES was applied for 30 min, suggesting that improvement of blood-flow control might be time-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Neuromodulation may vary depending on the duration, intensity, and area of application 16 . Previous studies have demonstrated that time of electrical stimulation seem to promote different responses, changes in local circulation 10,[17][18][19] , increase in myocardial oxygen, and reduction in oxygen demand 20 ; however, it is still unclear whether interferential current stimulation can improve blood flow during muscle metaboreflex induction. Indergand and Morgan 10 applied IES for only 10 min 10 , but in our study, the opposite results were obtained when IES was applied for 30 min, suggesting that improvement of blood-flow control might be time-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased vascular resistance may reduce myocardial oxygen consumption and therefore improves oxygen demand/consumption balance. Interesting findings were published by Hallén et al -in their study TENS caused vasodilation only in healthy control patients but not in those with the refractory angina 71 .…”
Section: Transcutaneous Electrical Nerve Stimulation (Tens)mentioning
confidence: 84%
“…Dong et al reported that the changes of perfusion and microcirculation in the stomach were effectively improved after EA given at the Zusanli (ST 36) acupoint [17]. One commonality found in many studies is that TENS has been identified as an effective treatment option to relieve ischemic pain by increasing local blood flow by inducing a vasodilatory effect [16]. In addition, another study also found that TENS can improve the vascular response of aged rats by producing a neurogenic vasodilator effect [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that TENS has become a novel complementary therapy and an alternative to conventional medicine in clinical practice because of its safety and lack of adverse reactions [14], [15]. Accumulating clinical and experimental evidence has demonstrated that TENS and electrical acupuncture stimulation can effectively increase local blood flow and blood perfusion to the stomach and reduce intestinal ischemia [16][18]. Additionally, it also can increase blood perfusion to the ovary by modulating central circulatory systems [19].…”
Section: Introductionmentioning
confidence: 99%